Last millennium hydroclimate in the central equatorial North Pacific (5°N, 160°W). (1st May 2021) - Sachs, Julian P.; Mügler, Ines; Sachse, Dirk; Prebble, Matthew; Wolhowe, Matthew
Abstract: Hydrogen isotope ratios ( 2 H/ 1 H or δ 2 H) were measured in lipid biomarkers from algal, plant and microbial sources in sediment cores from a lake and a peat bog on the small, sparsely-inhabited Washington Island (4°43′N, 160°25′W) to assess central equatorial Pacific hydroclimate conditions during the last millennium. High δ 2 H values in lipids from a variety of biological sources indicate that the driest period of the last millennium occurred ∼1450–1600 CE, during the first half of the Little Ice Age (LIA; 1450–1850 CE). An Intertropical Convergence Zone (ITCZ) located south of its modern position, less frequent and/or weaker El Niño events, and/or a La Niña-like mean state in the tropical Pacific are potential causes for this drying at Washington Island. From ∼1600 to 1650 CE, an abrupt transition to modern-like low δ 2 H values in phytoplankton, plant, and microbial lipids occurred, signaling the establishment of a high-rainfall regime similar to that observed today. This transition coincided with increased ENSO variability, an excess of central-Pacific relative to eastern-Pacific El Niños, and a decline in the zonal SST gradient across the tropical Pacific, reflecting an El Niño-like mean state. The Medieval Warm Period (MWP; 900–1250 CE) was characterized by high δ 2 H values in lipids from phytoplankton (dinosterol, dinostanol), bacteria (hop-21-ene), and vascular plants (sitostanol), and by extension a drier climate relative to the modern lake. An increasing δ 2 H trend through the MWP in lipids from all sources implies drying as Northern Hemisphere temperatures declined from the early to the late MWP. This drying is hypothesized to have been driven by extensive volcanism in northern, southern, and tropical latitudes, all of which tend to cause zonal mean drying at the latitude of WI (5°N). Finally, the transition period between the LIA and MWP ∼1250–1450 CE was characterized by declining δ 2 H values of plant and microbial lipids in peat sediments, indicating a trend toward wetter conditions; in the absence of known internal or external climate forcings, this may have been a regional or local event. This study demonstrates that the application of compound-specific δ 2 H measurements of lipids from multiple biological sources and in multiple sedimentary archives from a single location can yield hydroclimate reconstructions with higher confidence than those based on single lipids. Such reconstructions are particularly important in the vast tropical Pacific, where few hydroclimate records exist. Highlights: Hydroclimate reconstructed from δ 2 H values of algal, plant & microbial biomarkers. Lake & peat bog sediment cores from Washington Island, central equatorial Pacific. Driest period of the last millennium was the early Little Ice Age 1450–1600 CE Abrupt transition to modern high-rainfall regime occurred 1600–1650 CE